The subduction of continental crust - insights from eclogite geochronology and petrology - Miladinova, Irena (Universitäts- und Landesbibliothek Bonn, 2019)
When continents collide slices of continental crust may be dragged down into the subduction zone to depths of up to 200 km. The most straightforward evidence for continental subduction refers to the presence of high-pressure (HP) and ultrahigh-pressure (UHP) eclogite terranes in many collisional mountain systems. In addition, as inferred from numerical modelling continental subduction provides a physically most consistent explanation for the formation and exhumation of these terranes. Reconstruction of the P-T-t paths of HP and UHP rocks can provide direct constraints on the thermo-mechanical processes in subduction zones. For that, a multidisciplinary approach is the most promising one for understanding the subduction dynamics as well as the mechanisms of continental convergence. Three case studies were performed on HP and UHP eclogite terranes following similar procedures: the Eoalpine high-pressure belt in the Eastern Alps (Austria and Italy), the Byala Reka Dome in the Eastern Rhodopes (Bulgaria) and the Lofoten basement in the Scandinavian Caledonides (Norway). High precision Lu-Hf geochronology was applied on eclogites and combined with characterization of the chemical zoning in garnet. Additionally, thermodynamic modelling was performed on each of the dated samples for constraining the metamorphic conditions. The Eoalpine belt includes (ultra)high-pressure rocks that crop out along a northwest-southeast trending line extending from the Texel Complex in Italy to the Pohorje Mountains in Slovenia. Dating of garnet growth during pressure increase was achieved by using Lu-Hf chronometry that yielded results between c. 100 and c. 90 Ma. This time span of c. 10 Ma suggests short-lived period of subduction. Combined with the already published data the estimated metamorphic conditions indicate a field gradient with increasing P and T from northwest to southeast where the rocks experienced UHP Eoalpine metamorphism. The oldest Cretaceous eclogites are found in the Saualpe-Koralpe area that comprises widespread ...